1988
DOI: 10.1128/jb.170.12.5806-5813.1988
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recombination occurring at SLP1 att sites

Abstract: SLPlINt is a conjugative Streptomyces coelicolor genetic element that can transfer to Streptomyces lividans and integrate site specifically into the genome of the new bacterial host. Recombination of SLP1 previously has been shown to occur within nearly identical 112-base-pair act sequences on the plasmid and host chromosome. We report here that both integrative recombination and intermolecular transfer of SLPlINt require no more than a 48-base-pair segment of the att sequence and that SLP1 transfer occurs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Sedlmeier and collaborators (204) proposed that the lack of tRNA genes with rRNA genes might be characteristic for all actinomycetes. Based on the first reports that initiator tRNAs from Streptomyces griseus and S. rimosus lack CCA ends (74, 128) and on later publications indicating that potential tRNA Pro , tRNA Thr , and tRNA Tyr genes associated with site-specific recombination in Streptomyces also lack CCA termini (132,143,197), Plohl and Gamulin (185) predicted that most, if not all, tRNA genes in S. rimosus do not encode a CCA terminus. At present, this prediction is still valid and in agreement with current analyses of the tRNA genes based on genome sequencing data.…”
Section: Trna Rrna and Gene Expression In S Rimosusmentioning
confidence: 99%
“…Sedlmeier and collaborators (204) proposed that the lack of tRNA genes with rRNA genes might be characteristic for all actinomycetes. Based on the first reports that initiator tRNAs from Streptomyces griseus and S. rimosus lack CCA ends (74, 128) and on later publications indicating that potential tRNA Pro , tRNA Thr , and tRNA Tyr genes associated with site-specific recombination in Streptomyces also lack CCA termini (132,143,197), Plohl and Gamulin (185) predicted that most, if not all, tRNA genes in S. rimosus do not encode a CCA terminus. At present, this prediction is still valid and in agreement with current analyses of the tRNA genes based on genome sequencing data.…”
Section: Trna Rrna and Gene Expression In S Rimosusmentioning
confidence: 99%
“…Similar experiments reported previously (18) failed to detect these free circular molecules in nonmating cells, leading to the conclusion that excision is induced by mating. While we found a 2-to 10-fold increase in the abundance of autonomous xis+ SLP1 molecules during mating, the presence of precisely excised SLP1 plasmids in nonmating cells indicates that mating is not required for excision.…”
Section: Discussionmentioning
confidence: 57%
“…It is now clear that because the attB site lies within the 3' end of a gene encoding a tRNAT3" essential for viability of S. lividans (29), at least part of the 112-bp homology is required to regenerate this gene upon integration. We have shown previously that no more than 48 bp of the 112-bp attB-attP homology is required for a sequence to function as an attB site (18). However, during construction of a substrate for excision assays, we found that, while the Int-expressing plasmid pSUM307 can promote integration of a plasmid that contains a 485-bp segment of SLP1 DNA flanking attP (pSUM317, Fig.…”
Section: Discussionmentioning
confidence: 71%
“…For example, a cross in which S. coelicolor A3(2) served as the donor and S. lividans 66 functioned as the recipient revealed the presence of a 17-kb plasmidogenic locus in the former (258). Upon transfer, the locus could exist in the recipient in three forms: transiently as a 17-kb plasmid containing all the genetic content present in the original locus, integrated at a specific site in the S. lividans chromosome (203,259,260), or as one of several smaller plasmids, 11 to 14.5 kb in size (153). In the smaller plasmids, genetic information for integration and maintenance was deleted.…”
Section: Effective Abundance Of Gene Copiesmentioning
confidence: 99%